Estudo etnofarmacológico das plantas medicinais utilizadas pela população com hipertensão arterial sistêmica da unidade de saúde de andorinhas no município de Vitória - Es - Carmo, Rodrigo Alves do (2006)
Introduction: The modern medicine is well developed in most of the world. However, most part of population in developing countries uses medicinal plants (MP) for treatment of several diseases, as the Systemic Arterial Hypertension (SAH), which is a serious problem of public health. The objective of this study was to do a detailed ethnofarmacologic analyses regarding MP used by the population bearered of SAH at Andorinhas Unit Health, Vitória-ES. Material and Methods: There were applied 625 ethnofarmacologics questionnaires, to identify the interviewees’ profile and the MP used separately or associated to medicines, as well as their use. At the end of the interview, antropometrics values (weigh and height) and blood pressure (BP) values were measured. After determinating BP values, the individuals who assumed been SAH bearers were classified according to the IV Brazilian Guidelines of Arterial Hypertension. It was also requested, a sample of plants used for future taxonomic identification of the species. Results: Most of the population was female (72%), and used more MP (58%) that the men (38%). 39% of the individuals were mestizo, 56,4% didn’t finish primary school, 30% had family’s salary up to 1 minimum wage (MW) and 38% had salary between 2 and 3 MW. People with salaries above 5 MW use less MP than those with salaries up to 1 MW, between 2 and 3 MW and between 3 and 5 MW. Most part of population was between 50 and 70 years old, whose medium age was of 59,61±12,72 years old. Most part of individuals that use MP are 50 and 79 years old. The most used MP by the individuals, in all levels of pressure were: Melissa officinalis (lemon balm), Sechium edule (chayote), Averrhoa carambola (star fruit), Rosmarinus officinalis (rosemary), Bauhinia aff. candicans (cow paw) and xvii Cymbopogon citratus (lemon grass), among others. Conclusions: Most of the individuals of the analysed population presents tensional levels out of the normality strip. Individuals of all tensional levels use MP as a SAH treatment form. MP are used separately or associated to medicines by individuals non-controlled BP, as well as, for those that possess the BP at normal limits